2014
DOI: 10.1097/md.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Clinical- and Cost-effectiveness of Telemedicine in Type 2 Diabetes Mellitus

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
167
1
14

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(191 citation statements)
references
References 62 publications
3
167
1
14
Order By: Relevance
“…A meta-analysis of 35 randomized controlled trials (RCTs) employing a heterogeneous selection of TH interventions revealed a significant, albeit slight, decrease in HbA1c in the intervention group compared to the control group. 15 In a recent Cochrane Database systematic review that only considered RCTs of interactive TH interventions that involved direct patient-provider interaction and was delivered in addition to, or substituting for, usual care compared with usual care alone found that in studies recruiting participants with diabetes (16 studies, N = 2768) those allocated to TH had lower HbA1c values (mean difference -0.31, 95% CI -0.37 to -0.24; p <0.00001) at a median of 9 months of follow-up. 16 Our findings also demonstrated that a single endocrinology consultation (independent of the modality) improved glycemic control and decreased the percentage of patients who had poorly controlled diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 35 randomized controlled trials (RCTs) employing a heterogeneous selection of TH interventions revealed a significant, albeit slight, decrease in HbA1c in the intervention group compared to the control group. 15 In a recent Cochrane Database systematic review that only considered RCTs of interactive TH interventions that involved direct patient-provider interaction and was delivered in addition to, or substituting for, usual care compared with usual care alone found that in studies recruiting participants with diabetes (16 studies, N = 2768) those allocated to TH had lower HbA1c values (mean difference -0.31, 95% CI -0.37 to -0.24; p <0.00001) at a median of 9 months of follow-up. 16 Our findings also demonstrated that a single endocrinology consultation (independent of the modality) improved glycemic control and decreased the percentage of patients who had poorly controlled diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…5 With regards to TH care for type 2 diabetes, a recent meta-analysis found that only 2 of 35 studies included assessment of cost-effectiveness. 15 Clearly more robust economic analyses of TH care are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Table 32 in Appendix 6 provides a summary of the AMSTAR results. Only three reviews were methodologically strong, 342,353,362 with the remaining 21 obtaining a score of ≤ 6, thus being rated as being of poor quality.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Taking into consideration the limited data surrounding the financial implications of telemedicine, some reviews were unable to draw any meaningful conclusions. 45,140,362 …”
mentioning
confidence: 99%
“…They reported that TM, compared to control therapy, resulted in a clinically and statistically significant difference in A1C of -0.37% (P < .001). 5 In 2015 Flodgren and colleagues performed a review of randomized controlled trials of TM outcomes diseases and of 93 studies that they identified, 21 we for diabetes. Among the diabetes TM studies, they found lower A1C levels in subjects allocated to TM than in controls with a difference of -0.31% (P < .00001) at a median of 9 months follow-up with a high certainty of evidence.…”
Section: Outcomes Of Tm Interventionsmentioning
confidence: 99%